Formation mechanism of local government green governance peer effect in China: evolution logic and basic experience - Gu, Hengsheng; Liu, Hongda (Frontiers in Environmental Science, 2025)
The historic convergence of the world situation and China’s development has set the stage for changes in the international environment that have not been seen in a century. In this context, the economic, political, cultural, and social crises are intertwined, and the traditional development that uses ecology and resources as consumables is unsustainable, and the resulting ecological crisis further amplifies the anxiety for social change. With the introduction of China’s comprehensive deepening reform strategy, green governance, as a critical platform to carry the transformation of the shaping of the governance system and the modernization of governance capacity, is in line with and integrated with the construction of the sustainable pattern, and has become a key initiative in response to various crises. While the enthusiasm and enthusiasm for green governance have surged dramatically in the process of its formation and extension, the homogenization of recent years has further widened the differences in development within regions. The convergence of green governance, which rejects the objective directives of the laws of development, has led to an increase in the scale of resource redundancy and a significant decrease in the green effectiveness of many local governments. This paper examines the formation mechanism of the peer effect of green governance in local governments and clarifies the continuity of green governance by sorting out the origins, main contents, and connotations of green governance in local governments. In this study, a scientific definition of green governance is distilled based on the core changes in green governance in the broader historical context. In addition, the study examines the peer effect of local governments in past administrative decisions, and through the analysis of its origins and connotations, clarifies the potential possibilities and environmental influences on local governments’ convergent decisions. On this basis, the study summarizes the senses, external manifestations, and characteristics of the green governance peer effect through the overlap of the green governance + administrative decision-making peer effect at the historical level and the potential correlation and interoperability mechanisms within the two. The study found that green governance is a comprehensive organizational framework activity under integrating various types of decision-making. The characteristic is that the peer effect of green management will encompass all kinds of past decision-making patterns and interest mechanisms. The behavior motivations behind the peer effect must be examined in the context of historical experience to promote increased green governance effectiveness.